Evolución normativa de la pensión de invalidez en el régimen de prestaciones sociales del magisterio Colombiano. (2020)
It is vitally important to identify the relevant aspects that characterize the system of social benefits of the Colombian Magisterium in the field of social benefits to which a teacher has the right, in particular, in relation to obtaining the disability pension. Thus, to establish what has been the normative evolution of the acquisition of this social benefit for the Colombian Magisterium, before 1991, and with the norms enshrined with the promulgation of the Constitution of 1991, and in particular the regulations that derive from the Application of Law 100 of 1993 and its statutory. Thus, it is necessary to ponder the rights and benefits that the normative evolution of the disability pension for the educators affiliated to the National Fund of social benefits of the Magisterium has represented for the Colombian teachers, as well as to identify the situations that may trigger an invalidity pension, whether it is a common origin disease, a professional illness, or a work accident that is framed within the panorama of occupational hazards. Keywords: Teachers social benefits system, normative evolution, disability pension, occupational disease, work accident, occupational hazards.